Phase-time analysis of the leakage impulse current of faulty line-post pin insulators. - Kim, C.J (IEEE Transactions on power delivery)
Leakage impulse current of the faulty insulators was experimentally studied. The leakage impulse current was characterized in terms of the phase-time base of the applied voltage. The study showed that the leakage impulse is observed only in a distinct location in phase-time space. Based on the findings, prioritized maintenance scheduling was proposed, which could be used for status monitoring of insulators and distribution feeders.